SKI: Strategic innovations and brand awareness for the laundromat industry in Thailand - Kirai, Sukree; Khangasri, Chamroen; Keawtatanawattana, Phuriphat; Sirinanthana, Apiwan (Edelweiss Applied Science and Technology, 2025)
This study explores the strategies and marketing communication innovations employed by Alliance Laundry Systems LLC to enhance brand awareness in the Thai laundromat market. Utilizing a mixed-method approach, the research combines qualitative interviews with quantitative surveys to analyze the perceptions of laundromat owners and customers. The findings reveal that digital platforms, particularly social media, play a crucial role in driving brand awareness and customer engagement. Customers highly value perceived quality, including high-tech washing machines, modern payment methods, and regular maintenance services. The study also highlights the importance of brand relationships and loyalty in influencing customer retention. Based on the research findings, the SKi Strategy is proposed, emphasizing product segmentation, distributor management, and innovative communication knowledge to drive business success. The strategy advocates for the integration of advanced technologies such as AI and mobile applications to enhance operational efficiency and customer convenience. The research concludes that the laundromat industry in Thailand is poised for significant growth, driven by urbanization, technological advancements, and changing consumer preferences. The findings offer valuable insights for laundromat operators, distributors, and manufacturers, providing a strategic roadmap for achieving a competitive advantage and long-term success in the evolving market landscape.